Text and atlas slit lamp biomicroscopy for assessment in cataract surgery - Toshniwal, Navneet (Jaypee Brothers Medical Publishers, 2014)
Examination of patients of cataract in predilated and postdilated pupil by torch light and slit lamp is very important. In every case silt lamp is the most important tool to see the patient in detail. This book will help to see the cases in Gross view, Slit view and Retroillumination. Gross view will give overall idea about anatomy and size of the eye, conjunctiva, cornea, anterior chamber, iris, pupil, pupillary reaction, and stage of cataract. Slit view will be helpful to see layers of every structure in oblique illumination. Most important in this examination is status of the cornea, anterior chamber depth, details of iris, pupil, curvature of anterior capsule, all layers of the lens means anterior capsule, cortex, epinucleus, nucleus, and posterior capsule.